Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

Disparities in COVID-19 infection rates across linguistic groups in long-term care homes in Ontario, Canada - Batista, Ricardo; Fitzgerald, Michael; Reaume, Michael; Kendall, Claire E.; Bjerre, Lise M.; Mahdavi, Roshanak; Imsirovic, Haris; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Helene; Hsu, Amy; Bouchard, Louise; et al. (BMC Public Health, 2026)
Background The COVID-19 pandemic has had a disproportionate impact on residents of long-term care facilities or nursing homes, characterized by significantly higher infection and mortality rates than in the general population. Previous research has highlighted significant disparities in COVID-19 outcomes, particularly among ethnic minorities. This study examines the association between belonging to a minority language community and COVID-19 infection rates in LTCFs in Ontario, Canada, at both the individual and facility levels. Methods We conducted a population-based retrospective cohort study of 85,367 LTC home residents in Ontario between January 15, 2019, and March 30, 2020, which we followed until March 31, 2021, using data from the Continuing Care Reporting System. We defined resident language (obtained from routine assessments in nursing homes) as English (Anglophone), French (Francophone), or other (Allophone), and we calculated a weighted average of languages spoken by residents in each LTC facility to determine the linguistic environment of the LTC facility. We calculated incidence rates of COVID-19 for each linguistic group, and we fitted multilevel logistic regression models to assess the main factors influencing the risk of COVID-19 infection, to account for individual-level and facility-level linguistic factors. Results The overall incidence of COVID-19 was 14.8%. The incidence of COVID-19 was higher among Allophones (23.6%) compared to Anglophones (13.1%) and Francophones (12.2%). Allophones in English homes (22.5%) showed significantly higher incidence rates compared to Anglophones (13.1%) and Francophones (11.0%) in these same homes. After adjusting for sociodemographic and clinical characteristics, the risk of COVID-19 remained significantly higher for Allophones compared to Anglophones (aOR 1.14, 95% CI 1.05–1.22), while residents living in language-discordant nursing homes had a non-significantly higher risk of COVID-19 (aOR 1.07, 95% CI 0.99–1.14). Conclusions Over the first two waves of the COVID-19 pandemic, the risk of COVID-19 infection in nursing homes was highest among residents whose primary language was a language other than English or French. The results of our study show that COVID-19 disproportionately affected populations living in minority linguistic communities. These findings may help informing public health interventions aimed at addressing the language barriers in long-term care in Ontario, and across Canada.